El Foro como sistema de comunicación e interacción - Martín de la Hoz, Pablo (Revista Complutense de Educación, 2007)
Nowadays forums are an Internet open space which is giving a communication relationship to users so long or deep that topic’s forum or users are requiring. Each forum has an own aim, and is supported by the virtual community involved in them, either by using the forum as an open space, a meeting point or an e-learning’s resource in online courses. In any case, forum is an asynchronous communication and interaction group space, and success factors depend on maintenance, user’s utilities, and task moderation applied on the forum as a strategy to maintain it. This article talks about this, forums have an internal process which is necessary to know in order to obtain in learning